How to manage radioiodine-refractory thyroid cancer in the era of precision medicine - Olga Karapanou; Grigoris Effraimidis; Marina Michalaki; Katerina Saltiki (Drugs in Context, 2026)
Differentiated thyroid cancer has a favourable clinical course. However, a minority of patients with distant metastases lose the ability for radioiodine uptake. In case of refractoriness, the implementation of local therapies, that is radiofrequency/cryoablation or embolization, stabilizes metastasis and delays disease progression. A wait-and-see strategy can be a viable option in slow disease progression. On the other hand, in symptomatic patients with progressive disease, the alternative is systemic therapy with tyrosine kinase inhibitors. Three multi- kinase inhibitors have been approved for this indication: lenvatinib and sorafenib as a first-line option and cabozantinib as a second-line option. Next-generation sequencing allows identification of somatic genetic alterations in tumour tissue, some of which are druggable. Thus, additional selective inhibitors have been approved: larotrectinib and entrectinib for NTRK+ tumours, selpercatinib and pralsetinib for RET+ tumours, and crizotinib, alectinib and lorlatinib for ALK+ tumours. Such a personalized approach increases clinical benefit whilst minimizing adverse events. Future studies should focus on the combination of tyrosine kinase inhibitors and immunecheckpoint inhibitors; currently, there is no strong evidence that redifferentiation strategies add clinical benefit in terms of overall survival or progression-free survival. Download the Plain Language Summary of this article: https://www.drugsincontext.com/plain-language-summaries/plain-language-summary-how-to-manage-radioiodine-refractory-thyroid-cancer-in-the-era-of-precision-medicine This article is part of the How to manage thyroid diseases: from autoimmunity to malignancy Special Issue: https://www.drugsincontext.com/special_issues/how-to-manage-thyroid-diseases-from-autoimmunity-to-malignancy